Pengaruh Umur, Tingkat Pengetahuan, Dan Sikap Bidan Praktik Swasta (BPS) Pada Penggunaan Partograf Acuan Maternal Neonatal Dalam Pertolongan Persalinan Normal Di Wilayah Dinas Kesehatan Kota Semarang - Indrawati, Tatik (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2009)
Background: Use of partograf to aid normal labour, very effective and cheap to monitor labour process. Partograf has proven effective in prevent long labour, decrease surgical operation midwifery and finally increase safety of the embryo. Base on the case, the research lutends to recite koranic verses what factors which influence private midwife practice toward using partograf to aid normal labour.Method: The kind of research is explanatory or confirmatory research. The Method which use is survey method with cross sectional approach. The research location is in official health city Semarang area. The research subject is private midwife practice in official health city Semarang area, total example 73 midwifes, base on inclution criteria, whereas cross check does in-depth interview, in a triangulation manner to the midwife partner. Organization firer of IBI (Ikatan Bidan Indonesia), expert in a certain field midwifery sector (Doctor SpOg),Kasubdin Kesehatan Keluarga (Head of Sub Official Health City) Semarang.Result: Analysis of the research used Univariat analysis with descriptive statistic. Bivariat analysis used Chi Square, whereas multivariat analysis used regression logistic test with aid program SPSS for windows 10.0. The result shows that there is no influence periods of work, kind education level, social environment, facility private midwife practice toward practice using of partograf. Appropriate result of logistic regression analysis with influence is age,knowledge level and attitude of private midwife practice to practice using partograf to aid normal Child birth. The most dominant variable is attitude.Keywords: behavior, private, midwife, partograf, labour